Association between Cerebral Palsy or Death and Umbilical Cord Blood Magnesium Concentration - Palatnik, Anna; Rouse, Dwight J.; Stamilio, David M.; McPherson, Jessica A.; Grobman, William A. (American Journal of Perinatology, 2015)
Objective This study aims to evaluate whether magnesium sulfate (MgSO4) infusion at the time of delivery or magnesium cord blood concentration is associated with cerebral palsy (CP) or death diagnosed by the age of 2 years.Methods Secondary analysis of data from a randomized trial of MgSO4 versus placebo for prevention of CP or death among offspring of women with anticipated preterm delivery. This study cohort included singleton, nonanomalous fetuses, whose mothers received MgSO4 as neuroprophylaxis. The primary outcomes were CP or death diagnosed by the age of 2 years.Results A total of 936 neonates (93 with CP or death, 843 controls) were included in the analysis. Infants in the group with CP or death had MgSO4 infusing at delivery at a similar frequency to that of controls (49 [52.7%] vs. 463 [54.9%], p = 0.68). Mean concentrations of cord blood magnesium, available for 596 neonates, also were not different between the two groups (2.7 ± 0.9 vs. 2.6 ± 0.9 mEq/L, p = 0.66, respectively). Multivariable analyses did not alter these findings.Conclusion Among the offspring of women exposed to MgSO4, in utero, neither MgSO4 infusion at the time of delivery nor magnesium cord blood concentration is associated with CP or death.
Keywords: cerebral palsy; cord blood; magnesium sulfate; preterm delivery